If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -27 = 4x + 33 Reorder the terms: -27 + 8x = 4x + 33 Reorder the terms: -27 + 8x = 33 + 4x Solving -27 + 8x = 33 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -27 + 8x + -4x = 33 + 4x + -4x Combine like terms: 8x + -4x = 4x -27 + 4x = 33 + 4x + -4x Combine like terms: 4x + -4x = 0 -27 + 4x = 33 + 0 -27 + 4x = 33 Add '27' to each side of the equation. -27 + 27 + 4x = 33 + 27 Combine like terms: -27 + 27 = 0 0 + 4x = 33 + 27 4x = 33 + 27 Combine like terms: 33 + 27 = 60 4x = 60 Divide each side by '4'. x = 15 Simplifying x = 15
| 140=90+m | | 12-4x=-5x+22 | | 12x^2+26x-10=0 | | 2(g+4)+5g-1= | | 3n+28=200 | | 0.75n+1.29=7.00 | | x(2x-5)(x^2-3)(5x^3-8)=0 | | -3x=-5x+22 | | 5x-31=2x+5 | | 7x-36=4x+5 | | 5y-[2(y+1)+2]=7z | | (4.6-8n)0.5=3.8 | | 4n-25=75 | | 2(4-x)+7x=13 | | 4x+4=7x-17 | | x+5.5y=x+y+81 | | 4(5a+16)=16(a-35) | | 3x^4-13x^2=10 | | 32n+120=720 | | 6x-29+2x+24=67 | | 4(1+8v)+5v=-255 | | 8y+25=4y-27 | | 4(1+8)+5v=-255 | | 2x-9-5x=17-3x-42+8x | | (1-v)(3v-7)=0 | | (6x^2+7x-3)-(-2x^2+4x-5)= | | y=3(2x+4) | | 4x^2-3x+7+2x^2+4x= | | 95=0.05s^2+1.1s | | 2(y-1)=3y+4 | | 0.75-18.50=0.65x | | 2f-6=2 |